2017
DOI: 10.1080/17453674.2016.1278113
|View full text |Cite
|
Sign up to set email alerts
|

Imaging investigations before referral to a sarcoma center delay the final diagnosis of musculoskeletal sarcoma

Abstract: Background and purposeThe use of point-of-care or local investigations before referral to specialist sarcoma centers as part of a fast-track diagnostic pathway varies, and may affect the time to diagnosis. We wanted to investigate differences in time intervals and proportion of malignancy in patients who were referred after initial diagnostic investigations were performed locally and in patients who were referred without these investigations.Patients and methodsWe included 545 consecutive patients who were ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…We noticed an improvement in referral to reference centers over time, from 24.2% of patients in 2010 to 55.6% in 2016. Many sarcoma specialists already warned physicians of the pitfalls of delayed referral, assessing the diagnostic pattern of patients regarding their first symptoms [2,8,[19][20][21][22][23][24]. The implementation of an expert network was one of the strategies proposed to improve efficient referral, avoid misdiagnosis, and organize a straightforward sequence of care.…”
Section: Discussionmentioning
confidence: 99%
“…We noticed an improvement in referral to reference centers over time, from 24.2% of patients in 2010 to 55.6% in 2016. Many sarcoma specialists already warned physicians of the pitfalls of delayed referral, assessing the diagnostic pattern of patients regarding their first symptoms [2,8,[19][20][21][22][23][24]. The implementation of an expert network was one of the strategies proposed to improve efficient referral, avoid misdiagnosis, and organize a straightforward sequence of care.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand that delays in diagnosis are different than delays in treatment—where the latter is the time elapsed after a diagnosis is known to the time of treatment. Studies have sought to detect reasons for delayed referrals of patients to sarcoma specialists, though focusing on how these delays in diagnosis affect patient survival—not delays in treatment . Delays in diagnosis have been shown to be a major cause for malpractice litigation.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature regarding time to definitive treatment of STS has mainly focused on delays in diagnosis . These studies have identified risk factors for delay in diagnosis and the effect it has on patient survival, though little progress has been made in shortening time to diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…It noted that 179 (69%) of 258 sarcoma patients were referred with alarming symptoms, while the remaining 79 sarcoma patients who were referred without alarming symptoms. Of them, seven were found accidentally on imaging, five were referred with suspected recurrence of a sarcoma, 64 were referred with a confirmed histological diagnosis, and three were referred for other reasons [ 6 ]. It was also noted that the sending of histological samples by primary care doctors delays the patient referral and the diagnosis of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%